1984
DOI: 10.1139/b84-171
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic potential of sun and shade Viola species

Abstract: The photosynthetic responses of a forest floor violet (Viola blanda) and a related meadow species (Viola flmbriatula) grown under controlled conditions were measured to test the prediction that these two species were photosynthetically shade and sun adapted, respectively. Based on their low photosynthetic and dark respiration rates, and low light saturation and compensation points, both violets can be classified as shade-tolerant. The forest species was photosynthetically and morphologically inflexible when gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…4), which were even lower than those observed in plants continuously grown tinder low irradiance. These results resemble those on plants of Sotanum dulcamara L. from shaded habitats (Gauht 1976), Sotidago virgaurea L. (Bjorkman and Holmgren 1966) and Viola species (Curtis 1984). The protein levels of the chloroplasts and the chlorophyll content decreased due to a lack of anti-photooxidants (Bjorkman 1981), and photoinhibition may have taken place in P. major ssp major (Fig.…”
Section: Phenotypic Plastkitj'supporting
confidence: 74%
“…4), which were even lower than those observed in plants continuously grown tinder low irradiance. These results resemble those on plants of Sotanum dulcamara L. from shaded habitats (Gauht 1976), Sotidago virgaurea L. (Bjorkman and Holmgren 1966) and Viola species (Curtis 1984). The protein levels of the chloroplasts and the chlorophyll content decreased due to a lack of anti-photooxidants (Bjorkman 1981), and photoinhibition may have taken place in P. major ssp major (Fig.…”
Section: Phenotypic Plastkitj'supporting
confidence: 74%
“…In other studies investigators have been unable to show that this one factor is of major importance (Morgan, 1971;Solbrig, Newell, and Kincaid, 1980). Descriptions of photosynthetic responses to light have been included in broader investigations of the ecology of certain understory herbs (e.g., Chabot and Chabot, 1977;Chabot, 1978;Kawano, Takasu, and Nagai, 1978;Jurik et al, 1979;Curtis, 1984), but in none ofthese species has light availability been shown to be ofoverriding significance from the physiological to the population level of response. Aster acuminatus is unusual in this respect.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of photosynthetic responses to low light have been conducted by a number of investigators (e.g., Bjorkman and Holmgren, 1963;Boardman, 1977;Chabot and Chabot, 1977;Gross and Chabot, 1979;Teramura and Strain, 1979;Young and Smith, 1980;Bazzaz and Carlson, 1982;Curtis, 1984). From these studies and others we understand a great deal about how plants respond to variation in light and how they can adapt to low light.…”
mentioning
confidence: 99%
“…Another attribute of a competitive plant is flexibility in growth patterns. Only some forest plants display such morphological flexibility (e.g., Packham and Willis, 1982); without it, their performance, when exposed, e.g., to high light, may be poor (Curtis, 1984). On the other hand, morphological flexibility, when it occurs, may compensate somewhat for less flexible photosynthetic behavior in forest plants (Bazzaz and Carlson, 1982;Young and Smith, 1979).…”
Section: Discussion-favorable Environments Formentioning
confidence: 99%